A Study On The Characteristics Of Waste-Based Geomaterials - Ahmad, Muhammad Munsif (2011)
In this research, wastes namely shredded rubber, rice husk, and oil palm empty fruit bunches (OPEFB) have been individually used with mortar mix to produce geomaterials that will function as filtration media. Mixes were prepared with weight ratios ranging from 1:2:0.5:0.01 to 1:2:0.5:0.20 for cement, sand, water, and shredded rubber respectively. Mixes for rice husk were of the same ratios as for shredded rubber. Finally, mixes for OPEFB were ranging from 1:2:0.5:0.01 to 1:2:0.5:0.05 for cement, sand, water, and OPEFB content respectively. More mixes involving shredded rubber and rice husks were prepared with foam added.